Impact of the Implementation of Mining Law Number 4 Year 2009 and Minister of Finance Regulation Number PMK - 6/PMK.011/2014 Regarding Export Duty and Export Duty Tariff to PT. Freeport Indonesia - Biran, Ludi Maulana; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2015)
Abstract. This final project is regarding the curiousness of the author on the sustainability of PT Freeport Indonesia (â€œPTFIâ€) if the new mining law, Law Number 4 Year 2009 and its implementing regulation, Minister of Finance Regulation No. PMK - 6/PMK.011/2014 are enacted. The reason is, the implementation of the above law and regulation required PTFI to spend huge amount of money to establish a new purification company (in PTFIâ€™s case is Smelter Company) and also disallowed PTFI to export its product. Since this is impacting the financial side of PTFI, its forecasted Financial Statement after the implementation of the said law and regulations should be assessed to find out whether PTFI will still provide financial benefit to its shareholders or not. Failed to satisfy the shareholders might provoke them to withdraw their investment that in its turn can stop PTFIâ€™s operation due to lack of financing.The assessment of PTFIâ€™s Financial Statement will use derivation of ratio analysis tools, DuPont Model Analysis and State Owned Company (â€œBUMNâ€) Scoring Method, to find out whether PTFIâ€™s Financial Performance after the implementation of those law and regulation is still favorable for the shareholders or not, compare to the financial performance before the implementation of the law and regulation. Since the result of the assessment is not favorable for the shareholders, new strategies to overcome this problem should be setup. The proposed projects of Increasing Sales, Cost Reduction, Regulation Suspension, and Export Tax Discount, would worth to try, since they are proven can boost the Financial Performance of PTFI. Further, these project could also close Financial Performance gap between the Financial Performance before the implementation of the Law No. 4/2009 and MoF Regulation No. PMK - 6/PMK.011/2014 and the Financial Performance after the issuance of those law and regulation. At the end, there is no reason for shareholders to withdraw their investment at PTFI.Keywords: Favorable Financial Performance, Shareholders Satisfaction, Sustainability